Employment effects of minimum wages - David Neumark (IZA World of Labor, 2014)
The potential benefits of higher minimum wages come from the higher wages for affected workers, some of whom are in low-income families. The potential downside is that a higher minimum wage may discourage employers from using the low-wage, low-skill workers that minimum wages are intended to help. Research findings are not unanimous, but evidence from many countries suggests that minimum wages reduce the jobs available to low-skill workers.
Keywords: J23; J38; 330; minimum wages; employment effects